Prenatal Group B Streptococcus Test Using Real-Time Polymerase Chain Reaction - Chi-Feng Wei; Bo-Ching She; Hung-Shuo Liang; Qing-Dong Ling; Chen-Yuan Tsai; Chih-Wei Yen; Hsueh-Yin Wu; Ming-Song Tsai (Taiwanese Journal of Obstetrics & Gynecology, 2009)
Objective: The aim of this study was to evaluate the percentage of pregnant women with negative Group B Streptococcus (GBS) screening results by culture at 35 weeks' gestation, who subsequently had positive GBS test results after 39 weeks' gestation. Materials and Methods: From 2006 to 2007, we recruited 150 pregnant women who received routine GBS culture screening at 35 weeks' gestation with negative results, and who had repeat cultures and real-time polymerase chain reaction (RT-PCR) tests for GBS after 39 weeks' gestation. Results: Two percent of pregnant women with GBS-negative results by culture screening at 35 weeks' gestation were GBS-positive at 39 weeks' gestation. Conclusion: It is necessary to perform a GBS test 4 weeks after an initial negative GBS culture at 35–37 weeks of gestation. RT-PCR provides a simple and rapid alternative method for detecting rectovaginal GBS colonization at the time of labor.